ChemInform Abstract: Potassium Thiocyanate as Source of Cyanide for the Oxidative α‐Cyanation of Tertiary Amines. Issue 30 (July 2015) - Wagner, Alexander; Ofial, Armin R.
Abstract KSCN is oxidized at the sulfur to produce a cyanide unit which is trapped by the co‐oxidized amines with formation of α‐aminonitriles.